Use of learning objects in the teaching of the Senos Law and the Cosines Law - Moura, Patricia de Souza; Lavor, Otávio Paulino (Educação Matemática Debate, 2021)
The teaching of Mathematics is presented in several contexts today, such as Trigonometry, which can be taught in an interdisciplinary and dynamic way. In this sense, it is proposed to investigate the teaching of Trigonometry, particularly with the Law of Sines and Cosines, using learning objects. In this investigation, an Investigative Teaching Sequence will be carried out, aided by a simulator of the PhET platform in order to integrate the contents of Trigonometry and Vectors. The results of the evaluative activity and the satisfaction requirement indicate that there was interaction between the students during the class, as well as satisfactory concepts, occurring the teaching and learning process, also showing that there is a relationship between Trigonometry and Vectors. Thus, it can be concluded that a PhET platform is an alternative to using Trigonometry, using Vectors.